Implementation of Biogas Project Assignment In Steam-Based Learning To Develop Students' Creativity - Rayendra Wahyu Bachtiar; Slamet Hariyadi; Ihsaniatun Nur Alifah (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2025)
The objective of this study is to explore the impact of a STEAM-based biogas project-based learning approach on the creativity of seventh-grade students at MTs Negeri 06 Jember. This study used a descriptive qualitative approach. It involved 25 students. The students were divided into three groups. For two weeks, students carried out a biogas prototyping project with different organic waste materials and varied fermentation methods. The research instruments included creativity observation sheets and LKPD assessment, with creativity indicators including originality of ideas, flexibility of thinking, integration across STEAM disciplines, visual expression, and perseverance. The results showed that all groups succeeded in developing a simple biogas model and obtained creativity scores and LKPD scores in the good to excellent category. STEAM project-based learning proved effective in improving students' creative thinking skills, understanding of science concepts, and environmental awareness. Thus, this approach is recommended to be applied in environment-based contextual learning at the junior high school level.